Effect of temperature on the life history of Cirrospilus sp. near lyncus (Hymenoptera: Eulophidae), a parasitoid of Phyllocnistis citrella (Lepidoptera: Gracillariidae) - Urbaneja, Alberto; Llácer, Elena; Garrido, Antonio; Jaques, Josep A. (2017)
The effect of four constant temperatures on the life history of Cirrospilus sp. near lyncus was examined in the laboratory. This species is one of the most abundant generalist indigenous parasitoids of the citrus leafminer, Phyllocnistis citrella Stainton, in Spain. Adult lifespan of C. sp. near lyncus decreased from 50.2 to 9.1 days as temperatures increased from 15 to 30°C, respectively. Both gross fecundity and host-feeding were highest at 20°C (170.48 eggs and 32.33 hosts). Oviposition rates were optimal at higher temperatures (5.22 eggs per day at 25°C and 4.79 eggs per day at 30°C) and were dependent on female age. In contrast, host-feeding rates for a given temperature did not depend on age. Generation time decreased with increasing temperatures from 68.05 days at 15°C to 12.19 days at 30°C. Net reproduction peaked at 20°C (68.86 viable females per female). Intrinsic rate of increase doubled from 15°C (0.059 females per female per day) to 20°C (0.127 females per female per day) and almost doubled again from 20 to 30°C (0.210 females per female per day). Given these parameters, C. sp. near lyncus could perform optimally in the area occupied by P. citrella in the Mediterranean region. © 2001 Academic Press.